2023
DOI: 10.3390/v15081645
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Virus Engineering and Utilizations: Cancer Immunotherapy Perspective

Abstract: Oncolytic viruses have positively impacted cancer immunotherapy over the past 20 years. Both natural and genetically modified viruses have shown promising results in treating various cancers. Various regulatory authorities worldwide have approved four commercial oncolytic viruses, and more are being developed to overcome this limitation and obtain better anti-tumor responses in clinical trials at various stages. Faster advancements in translating research into the commercialization of cancer immunotherapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 192 publications
0
2
0
Order By: Relevance
“…Oncolytic viruses selectively infect cancer cells and eventually lyse them without infecting healthy cells [ 42 ]. In fact, glioma cells were destroyed by oncolytic viruses [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic viruses selectively infect cancer cells and eventually lyse them without infecting healthy cells [ 42 ]. In fact, glioma cells were destroyed by oncolytic viruses [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high transfection efficiency and the development of vector engineering techniques, OVs have been widely used and showed promising results in preclinical and clinical studies in GB (see [ 843 , 856 , 857 ] for a recent review). In addition, OVs have many advantages over conventional immunotherapies, including precise targeting, effective killing rates, and minimal adverse reactions [ 858 ]. To date, several clinical trials have been carried out for oncolytic viruses to improve the treatment of GB [ 836 , 843 , 857 ].…”
Section: Immunotherapiesmentioning
confidence: 99%
“…7 OVs encompass both naturally occurring and genetically engineered viruses, with the latter showing enhanced efficacy and improved targeting capabilities. 8 OVs can reproduce within tumor cells, generating additional offspring virions that destroy neighboring tumor cells through various mechanisms, including direct lysis of tumor cells, stimulation of local or systemic immune responses against the tumor, and modification of the tumor microenvironment. 9 Several studies have demonstrated significant antitumor effects of oncolytic vaccinia virus containing Aphrocallistes vastus lectin in HCC cells and mouse models with transplanted human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that SVA has a strong capability to target tumors with neuroendocrine characteristics. 8 A solitary intravenous administration of the oncolytic picornavirus SVV-001 eradicated medulloblastomas in primary tumor-derived orthotopic xenograft mouse models. 16 Surprisingly, the administration of 10 14 vp/kg of the oncolytic virus SVV-001 successfully eradicated tumors in two out of six heterotransplant mouse models of a specific small cell lung cancer variant, with long-lasting effects.…”
Section: Introductionmentioning
confidence: 99%